Pengaruh Latihan Lompat Dengan Rintangan Dan Meraih Sasaran Di Atas Terhadap Kemampuan Lompat Jauh Gaya Jongkok Pada Siswa Kelas VII 3 SMP Negeri 1 Mare Kabupaten Bone - yappa yappa (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2019)
The problem of this research is: Is there a difference in the effects of exercise jumping obstacles and achieve goals on the ability of the long jump at the Class VII student SMP Negeri 1 Mare. The research objective to declare the presence and absence difference in the effects of exercise jumping obstacles and achieve the above targets. The research method uses an experimental method with the M-S pattern. This study population Class VII student SMP Negeri 1 Mare amounting to 24 students. The research instrument used was the squat style long jump test. Data analysis using the t-test. The results showed that t count> t-table or 2.4620> 2.201 with a significant level of 5% to 11 dB means that there is a significant difference between the exercise jumping obstacles and achieve goals on the ability of the long jump at Seventh Grade 3 student of SMP Negeri 1 Mare. From the calculation of the mean, indicating that the first experimental group means is greater than the mean of the experimental group 2 (318.67> 308.17), thereby exercise hurdle jump with better results compared with the exercise achieve the above targets. To see the results, it is suggested to Penjas teachers and trainers to improve the long jump ability can squat exercise style jump with the hurdle